STRATEGI PEMASARAN BUKU KARYA KH DJAMALUDDIN AHMAD: STUDI KASUS PADA PUSTAKA AL MUHIBBIN BAHRUL ULUM JOMBANG - Muhammad Ulil Maulana; Corry Asmarany, S.IIP,.M.A (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstrack. This study aims to describe the book marketing strategies implemented by Pustaka Al-Muhibbin Bahrul Ulum Jombang and to identify the supporting and inhibiting factors based on the 7P marketing mix perspective. The research utilizes a descriptive qualitative approach, with data collection techniques consisting of interviews, observation, and documentation, which were then analyzed through descriptive analysis. The results indicate that Pustaka Al-Muhibbin implements an integrated 7P marketing mix strategy by providing religious books with literacy and dawah value, setting affordable prices, selecting strategic sales locations supported by digital channels, and conducting promotions through print media and marketplaces. The elements of people, process, and physical evidence are also optimized through the involvement of human resources who understand the book contents, ease of the purchasing process, and the strengthening of visual identity and store appearance. The primary supporting factors include the author's figure and the Islamic boarding school (pesantren) alumni network, while the inhibiting factors include suboptimal digital promotion, limited human resource training, and book stock management. Keywords: marketing mix; book marketing; Islamic boarding school (pesantren); marketing strategy; 7P Abstrak. Penelitian ini bertujuan mendeskripsikan strategi pemasaran buku yang diterapkan Pustaka Al-Muhibbin Bahrul Ulum Jombang serta mengidentifikasi faktor pendukung dan penghambatnya berdasarkan perspektif bauran pemasaran (7P). Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi, yang dianalisis melalui analisis deskriptif. Hasil penelitian menunjukkan bahwa Pustaka Al-Muhibbin menerapkan strategi bauran pemasaran 7P secara terpadu melalui penyediaan buku keagamaan bernilai literasi dan dakwah, penetapan harga terjangkau, pemilihan lokasi penjualan strategis yang didukung kanal digital, serta promosi melalui media cetak dan marketplace. Unsur people, process, dan physical evidence juga dioptimalkan melalui keterlibatan SDM yang memahami konten buku, kemudahan proses pembelian, serta penguatan identitas visual dan tampilan toko. Faktor pendukung utama meliputi figur pengarang dan jaringan alumni pesantren, sedangkan faktor penghambat mencakup promosi digital yang belum optimal, keterbatasan pelatihan SDM, dan manajemen stok buku. Kata Kunci: bauran pemasaran; pemasaran buku; pesantren; strategi pemasaran; 7P